A New Approach of Tank Cleaning Robot - Vasumathi, G. (International Journal of Psychosocial Rehabilitation, 2018)
In today’s world to clean a storage tank is quite very tiresome. Every work has to be done manually. Due to the great height work may be very risky. Hence there is a need to use a robot for cleaning purpose. Here we tried to develop a system where the robot can control remotely by the user. The paper presented is basically a survey made on underwater robot.